Economic Unions and the Gravity Model: Evidence from Eurasian Economic Union - Tumanyan , Robert (Asian Journal of Empirical Research, 2018)
The purpose of this study is to analyze trade creation and trade diversion effects in the Eurasian Economic Union (EEU), which is an evolution of regional trade agreements. The research will analyze intra-block trade flows and test trade creation and diversion in EEU determined by customs union agreements. Gravity model has been applied to annual bilateral export flows for EEU countries paired with a sample of 58 partner countries in the period of 2005-2016, using augmented gravity model with panel year fixed effect, this paper analyzes trade creation and diversion effects of EEU in general. The results are similar to other identical studies and suggest that EEU is mostly trade-diverting with a minor effect of trade creation.